The Effect of Rentability Ratio, Solvability Ratio, Liquidity Ratio upon the Company’s Value (Emperical Study of Mining companies Sub Sector of Metal and Other Mineral Registered in The Indonesia Stock Exchange in 2012 – 2016) - Gilang Ramadhan Fajri (The Accounting Journal of Binaniaga, 2018)
This research is an empiric study to examine The Effect of Rentability Ratio, Solvability Ratio, Liquidity Ratio upon the Company’s Value (Empiric Study of the Mining Company, Sub Sector Metal and other Mineral registered in the Indonesia Stock Exchange in 2012 – 2016) and sampling technique has applied purposive sampling which are 7 of 9 companies registered in the Indonesia Stock Exchange. The objective of this research is to prove the Effect of Solvability ratio, Liquidity ratio and Rentability ratio upon the Company’s value measured by Price Book Value (PBV) and which variables have been more dominantly affecting Price Book Value (PBV) The analysis techniques which have been used in this research are classical assumption, multiple linear regression and hypothesis test using t-statistic to examine partial regression coefficient and f-statistic to examine the reliability of the research model using level of significance of 10%. Moreover, the examination of classical assumption test has been covering normality test, multicolinierity test, heteroscedasticity test and autocorrelation test, the effect of independent variable upon dependent variable refers to the company’s book value (PBV) which is only 0.17 or equals to 17%. However the remaining value of 0.83 or equals to 83% has been described by other variables which are not included in this research and the result of the research of the variables being used for the period of variable debt to assets (DAR) which has been most dominantly affecting the company’s value of 0.627 or 62.7 %.Keywords  :  Gross Profit Margin (GPM), Return On Equity (ROE), Debt to Equity Ratio (DER), Debt to Asset Ratio (DAR), Current Ratio, Price Book Value (PBV).